2015
DOI: 10.1038/jhh.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure levels and control in Italy: comprehensive analysis of clinical data from 2000–2005 and 2005–2011 hypertension surveys

Abstract: This analysis is aimed to determine blood pressure (BP) levels and BP control rates in a large population of hypertensive patients in Italy. Data were taken from two large and inclusive cross-sectional surveys, which covered two distinct and subsequent time periods (2000-2005 and 2005-2011, respectively). Observational clinical studies and surveys, which reported average systolic/diastolic clinic BP levels, proportions of treated/untreated and controlled/uncontrolled patients, and prevalence of cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
64
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 26 publications
11
64
0
8
Order By: Relevance
“…2,4,5,7 Several studies have shown that in some countries the prevalence of hypertension has been generally stable and that a significant improvement in hypertension management has occurred during the past few decades. [8][9][10][11][12][13][14][15] However, some studies have found no recent progress in BP control, 16,17 and it has been questioned whether a favorable trend is actually occurring in the population. 18 Discrepancies in results among studies might be partly because of the use of different settings and procedures for BP measurement.…”
mentioning
confidence: 99%
“…2,4,5,7 Several studies have shown that in some countries the prevalence of hypertension has been generally stable and that a significant improvement in hypertension management has occurred during the past few decades. [8][9][10][11][12][13][14][15] However, some studies have found no recent progress in BP control, 16,17 and it has been questioned whether a favorable trend is actually occurring in the population. 18 Discrepancies in results among studies might be partly because of the use of different settings and procedures for BP measurement.…”
mentioning
confidence: 99%
“…Despite a solid and undisputable evidence of the efficacy of antihypertensive treatment in cardiovascular prevention, the awareness, treatment and control of elevated BP values are still low in most industrialized countries, including Italy [3][4][5][6][7][8]. Poor BP control rates have been reported also by large observational studies and clinical surveys, performed in different clinical settings and in different countries.…”
mentioning
confidence: 99%
“…Poor BP control rates have been reported also by large observational studies and clinical surveys, performed in different clinical settings and in different countries. The lack of BP control translates in a significant increase in the incidence of stroke, coronary artery disease, heart failure and chronic kidney disease.Recent data collected in several European countries and in Italy have shown that among treated patients only about 30 % reach an adequate BP control [3][4][5][6][7][8]. In Italy it has been documented that in years between 2005 and 2011 only 60 % of subjects with high BP are treated and among them the reduction of BP below 140/90 mHg is observed in 37 %.…”
mentioning
confidence: 99%
See 2 more Smart Citations